Contralateral effects after unilateral strength training: A meta-analysis comparing training loads - Fisher, J. P. (Journal of Sports Science & Medicine, 2018)
In summary, authors should be cautious of the use of meta-analyses both in research and application. As highlighted herein, numerous methodological inconsistencies are present and demonstrate the heterogeneity within the studies included in this meta-analysis. For a meta-analysis to be valid there needs to be a large number of homogenous studies, something which appears to be lacking within resistance training and notably, within the specialised area of cross-education. A more qualitative review of the literature might have better discussed the methodological details as well as highlighting areas for replication studies and progressive research, rather than attempt to draw general conclusions from considering only the numerical values. Furthermore a practical understanding and explanation of the training and testing methods is essential to ensure that studies are fairly represented.